A comparison between virus- versus patients-centred therapeutic attempts to reduce COVID-19 mortality - Serge Camelo; Mathilde Latil; Sam Agus; Waly Dioh; Stanislas Veillet; René Lafont; Pierre J. Dilda (Emerging Microbes and Infections)
Since December 2019, coronavirus disease 2019 (COVID-19), caused by infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has changed our lives. Elderly and those with comorbidities represent the vast majority of patients hospitalized with severe COVID-19 symptoms, including acute respiratory disease syndrome and cardiac dysfunction. Despite a huge effort of the scientific community, improved treatment modalities limiting the severity and mortality of hospitalized COVID-19 patients are still required. Here, we compare the effectiveness of virus- and patients-centred strategies to reduce COVID-19 mortality. We also discuss the therapeutic options that might further reduce death rates associated with the disease in the future. Unexpectedly, extensive review of the literature suggests that SARS-CoV-2 viral load seems to be associated neither with the severity of symptoms nor with mortality of hospitalized patients with COVID-19. This may explain why, so far, virus-centred strategies using antivirals aiming to inhibit the viral replicative machinery have failed to reduce COVID-19 mortality in patients with respiratory failure. By contrast, anti-inflammatory treatments without antiviral capacities but centred on patients, such as dexamethasone or Tocilizumab®, reduce COVID-19 mortality. Finally, since the spike protein of SARS-CoV-2 binds to angiotensin converting enzyme 2 and inhibits its function, we explore the different treatment options focussing on rebalancing the renin-angiotensin system. This new therapeutic strategy could hopefully further reduce the severity of respiratory failure and limit COVID-19 mortality in elderly patients.